Modern Statistics for the Life Sciences: Learn to Analyse Your Own Data - Alan Grafen; Rosie Hails (Oxford University Press, 2008)
Home > Education > Modern Statistics for the Life Sciences Modern Statistics for the Life Sciences Learn to analyse your won data by Alan Grafen ISBN (Paperback): 0199560404, 9780199560400 Price (Paperback): 280.00 INR [Add To Cart] Pages: 368 Language: English Year of Pub.: 2008 Bookmark and Share ABOUT THE BOOK: This text book teaches statistics in a different way. It is aimed at undergraduate students in the life sciences, and it will also be invaluable for many graduate students. It makes the powerful methods of model formulae and the General Linear Model accessible to undergraduates for the first time. This text presents the fundamental statistical concepts without being tied to any one statistical package. Three supplements available on the web site provide all the information students need to conduct the analyses in Minitab , SAS, or SPSS. All datasets are available on the web site.
Keywords: Mathematical statistics